Effect of Anticoagulation on The Hepatic Function of Non-Malignant Portal Vein Thrombosis (Journal of Fatima Jinnah Medical University, 2024)
Background: In various groups of PVT patients, portal vein thrombosis (PVT) occurs at a rate of 5-26%; the incidence increases with progressive liver disease. Portal vein thrombosis increases portal hypertension, increases the risk of variceal haemorrhage, and decreases hepatic perfusion, eventually leading to hepatic decompensation. Therefore this study is conducted toevaluate the effect of anticoagulation on the hepatic function of non-malignant portal vein thrombosis.Patients and Methods: Total 200 patients were consecutively enrolled in this retrospective study among April 2021 to April 2022. Patients with malignant PVT and those who lacked enough clinical data at the time of PVT diagnosis and during the subsequent clinical course were excluded. Retrospective analysis was used in this study to assess how anticoagulation affected hepatic function. A predesigned proforma were used to collect data. All the data was entered and analyzed by SPSS version 25. All the quantitative variables were presented by Mean+ SD and qualitative with frequency and percentages. An independent sample t test was applied to find out the significant difference of hepatic function among groups. P-value< 0.05 was considered as significant.Results: Total 200 patients were enrolled in current study among which 100 were treated with anticoagulation and 100 without anticoagulation. The mean age among groups were (T= 48.99+1.73 Vs. UT=49.50+1.63). Majority of the patients were male (115/200) and married (161/200). Majority of patients were Males, Married, normal weighted (123/200), moderate ascites (55/200), grade 3 hepatic encephalopathy (105/200) and child PUGH class A (97/200). There was insignificant mean difference of hepatic function among groups. The ALT, AST ALP, Albumin, Bilirubin shows insignificant difference (P-value>0.05).Conclusion: Our research shows that anticoagulation reduces hepatic damage and enhances liver production in people with non-malignant PVT.
Keywords: Anticoagulation; Hepatic Function; Portal Vein Thrombosis